From Dopdi to Draupadi, from Oppression to Empowerment: Reading Mahashweta Devi2019;s Draupadi (Global Journal of Human-Social Science, 2021)
The subaltern stories by Mahasweta Devi by refusing to conform to the conventions of the Indian literary canon have blatantly exposed the grim realities of the interplay of caste and class in the fabric of Indian society and as Rangrao Bhongle rightly asserts have projected an unknown facet of social reality in the Indian context The paper seeks to study Draupadi a short story by Mahashweta Devi and translated by Gayatri Chakravorty Spivak in 1988 which recreates the episode of The Mahabharata in which Draupadi the wife of the five Pandavas was asked to be stripped naked but was finally saved by Lord Krishna Draupadi Dopdi Mejhen the leader of Operation Bakuli in the story is caught by the police and raped by many While no God comes to save her she at the end derives strength from her naked body and finally stands as an empowered woman a terrifying superobject Spivak in front of Senanayak the man who sanctioned her rape and who stands like an unarmed target Spivak in a state of paralysis
Keywords: dalit; empowerment; nakedness; oppression